Global transcriptomic analysis reveals candidate genes associated with different phosphorus acquisition strategies among soybean varieties - Yang, Tongli; Yang, Songhua; Chen, Zhu; Tan, Yuechen; Bol, Roland; Duan, Honglang; He, Jin (Frontiers in Plant Science, 2022)
Soybean adapts to phosphorus-deficient soils through three important phosphorus acquisition strategies, namely altered root conformation, exudation of carboxylic acids, and symbiosis with clumping mycorrhizal fungi. However, the trade-offs and regulatory mechanisms of these three phosphorus acquisition strategies in soybean have not been researched. In this study, we investigated the responses of ten different soybean varieties to low soil phosphorus availability by determining biomass, phosphorus accumulation, root morphology, exudation, and mycorrhizal colonization rate. Furthermore, the molecular regulatory mechanisms underlying root phosphorus acquisition strategies were examined among varieties with different low-phosphorus tolerance using transcriptome sequencing and weighted gene co-expression network analysis. The results showed that two types of phosphorus acquisition strategies—“outsourcing” and “do-it-yourself”—were employed by soybean varieties under low phosphorus availability. The “do-it-yourself” varieties, represented by QD11, Zh30, and Sd, obtained sufficient phosphorus by increasing their root surface area and secreting carboxylic acids. In contrast, the “outsourcing” varieties, represented by Zh301, Zh13, and Hc6, used increased symbiosis with mycorrhizae to obtain phosphorus owing to their large root diameters. Transcriptome analysis showed that the direction of acetyl-CoA metabolism could be the dividing line between the two strategies of soybean selection. ERF1 and WRKY1 may be involved in the regulation of phosphorus acquisition strategies for soybeans grown under low P environments. These findings will enhance our understanding of phosphorus acquisition strategies in soybeans. In addition, they will facilitate the development of breeding strategies that are more flexible to accommodate a variety of production scenarios in agriculture under low phosphorus environments.